A Porous TiAl6V4 Implant Material for Medical Application. (16th October 2014) - Deing, Axel; Luthringer, Bérengère; Laipple, Daniel; Ebel, Thomas; Willumeit, Regine
Abstract : Increased durability of permanent TiAl6V4 implants still remains a requirement for the patient's well-being. One way to achieve a better bone-material connection is to enable bone "ingrowth" into the implant. Therefore, a new porous TiAl6V4 material was produced via metal injection moulding (MIM). Specimens with four different porosities were produced using gas-atomised spherical TiAl6V4 with different powder particle diameters, namely, "Small" (<45 μ m), "Medium" (45–63 μ m), "Mix" (90% 125–180 μ m + 10% <45 μ m), and "Large" (125–180 μ m). Tensile tests, compression tests, and resonant ultrasound spectroscopy (RUS) were used to analyse mechanical properties. These tests revealed an increasing Young's modulus with decreasing porosity; that is, "Large" and "Mix" exhibit mechanical properties closer to bone than to bulk material. By applying X-ray tomography (3D volume) and optical metallographic methods (2D volume and dimensions) the pores were dissected. The pore analysis of the "Mix" and "Large" samples showed pore volumes between 29% and 34%, respectively, with pore diameters ranging up to 175 μ m and even above 200 μ m for "Large." Material cytotoxicity on bone cell lines (SaOs-2 and MG-63) and primary cells (human bone-derived cells, HBDC) was studied by MTT assays and highlighted an increasing viability with higher porosity.